Cluster stochastic synchronization of complex dynamical networks via fixed-time control scheme. (April 2020) - Zhang, Wanli; Li, Chuandong; Li, Hongfei; Yang, Xinsong
Abstract: By means of fixed-time (FDT) control technique, cluster stochastic synchronization of complex networks (CNs) is investigated. Quantized controller is designed to realize the synchronization of CNs within a settling time. FDT synchronization criteria are established with the help of Lyapunov functional and comparison system methods. It should be noted that the convergence of synchronization is further improved by comparing with existing FDT synchronization results. Numerical simulations are given to illustrate our results.